Including Surgical Resection in the Multimodal Management of Very Locally Advanced Sinonasal Cancer. (28th December 2021) - Karp, Jerome M.; Hu, Kenneth S.; Persky, Michael; Persky, Mark; Jacobson, Adam; Tran, Theresa; Li, Zujun; Givi, Babak; Tam, Moses M.
Abstract : Objective: Sinonasal cancer often presents as locoregionally advanced disease. National guidelines recommend management of stage T4b tumors with systemic therapy and radiotherapy, but recent studies suggest that including surgical resection in the multimodal treatment of these tumors may improve local control and survival. We queried the National Cancer Database to examine patterns of care and outcomes in T4b sinonasal squamous cell carcinoma (SCC). Study Design: Prospectively gathered data. Setting: National Cancer Database. Methods: Patients with T4b N0‐3 M0 sinonasal squamous cell carcinoma diagnosed in 2004 to 2016 were stratified between those who received chemoradiotherapy and those who underwent surgical resection with neoadjuvant or adjuvant treatment. The overall survival of each cohort was assessed via Kaplan‐Meier analysis and Cox proportional hazard models, with repeat analysis after reweighting of data via inverse probability of treatment weighting. Results: Among 805 patients included in analysis, 2‐year overall survival for patients undergoing surgical resection was 60.8% (95% CI, 56.1%‐65.9%), while for patients undergoing chemoradiotherapy it was 46.7% (95% CI, 41.9%‐52.0%). On Cox regression analysis, the inclusion of surgery in management was associated with improved survival in univariate analysis (hazard ratio [HR], 0.723 [95% CI, 0.606‐0.862]; P <. 001) and multivariate analysis (HR, 0.739 [95% CI, 0.618‐0.885]; P =. 001). Results with reweighted data were consistent in univariate analysis (HR, 0.765 [95% CI, 0.636‐0.920]; P =. 004]). Conclusion: Surgical treatment with neoadjuvant or adjuvant treatment for stage T4b sinonasal SCC was associated with promising survival outcomes, suggesting a role for incorporating surgery in treatment of select T4b SCC, particularly when removal of all macroscopic disease is feasible.